Building Bridges: Understanding the Interplay between Generation X, Generation Y, and Generation Baby Boomers – Characteristics, Organisational Culture, and Organisational Identification in Modern Cities - Kam, Aygün (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
Over the years, the profile of a modern city dweller has been evolving and diversifying due to the emergence of various generations. Different generations are characterised by distinct expectations and perspectives towards life. Therefore, in today’s highly dynamic environment, city authorities must deeply understand their city dwellers to build an influential organisational culture which will lead them to have city friendly citizens in order to create resilient, sustainable, and inclusive cities. This study aims to define the impact of Generation X, Generation Y, and Generation Baby Boomers employees’ characteristics on organisational culture and organisational identification relationships in terms of professional and urban life. From this perspective, a study was carried out on 460 white-collar employees who are city dwellers working stationary in the private sector in Istanbul. The data were obtained in the course of a quantitative study carried out through an interview questionnaire using the CAPI (Computer Assisted Personal Interview) technique. The primary conclusions are that there is a statistically significant and positive relationship between clan (β = 0.360, p < 0.01) as well as market (β = 0.147, p < 0.05) culture and organisational identification. In addition, there is a statistically significant relationship between employees’ experience levels and their perceptions of adhocracy culture (F = 3.19, p < 0.05), and there is no statistically significant difference between the perceptions of Generation X, Y, and Baby Boomers employees about organisational culture and organisational identification levels.